1987
DOI: 10.1017/s0001566000004591
|View full text |Cite
|
Sign up to set email alerts
|

The Vietnam Era Twin (VET) Registry: Method of Construction

Abstract: Abstract. A Vietnam Era (1964-1975 Twin Registry of American male-male veterans born between 1939 and 1955 has been developed to provide a study sample for research evaluating the impact of Vietnam service on the medical and psychosocial aspects of health. In preparation for developing the Registry, several alternative sources of twins and methods for identifying twins were investigated. A computerized database of veterans discharged from the military after 1967 was selected as the source because it contains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(184 citation statements)
references
References 6 publications
0
184
0
Order By: Relevance
“…A complete description of the registry's construction (Eisen et al 1987 ;Henderson et al 1990) and method of determining zygosity have been previously reported (Eisen et al 1989).…”
Section: Methods Subjectsmentioning
confidence: 99%
“…A complete description of the registry's construction (Eisen et al 1987 ;Henderson et al 1990) and method of determining zygosity have been previously reported (Eisen et al 1989).…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Combat severity was assessed using a standard 18-item combat exposure measure 42 . Complete descriptions of the development and characteristics of the VET Registry have appeared elsewhere 43,44 . All subjects had previously participated in a larger twin study of PTSD at our laboratory; a full description of the recruitment strategy appears elsewhere 45 .…”
Section: Subjectsmentioning
confidence: 99%
“…(APA, 1980(APA, , 1987(APA, , 1994. Datasets VA = Veterans Affairs, NCS = National Comorbidity Survey (NCS; Kessler et al, 1994), BRFSS = Behavioral Risk Factor Surveillance System (Remington et al, 1988), VET Registry = Vietnam Era Twin Registry (Eisen et al, 1987), Boston Veterans Affairs Normative Aging Study (Bosse et al, 1984), NWS = National Women's Study . Smoking, PTSD, and Trauma Measures HRA = Health Risk Appraisal (HRA; University of Michigan, 1996), FTND = Fagerstrom Test for Nicotine Dependence (FTND; Heatherton et al, 1991), FTQ = Fagerstrom Tolerance Questionnaire (Fagerstrom, 1978), K-SADS-PL = Schedule for Affective Disorders and Schizophrenia for School Aged Children -Present and Lifetime version (Kaufman et al, 1997), DIS = Diagnostic Interview Schedule (DIS; Robins et al, 1981), Personal Experience Screening Questionnaire (Winters, 1991), CIDI = Composite International Diagnostic Interview (CIDI; World Health Organization Version 1.0), modified Smoking Withdrawal Questionnaire (Shiffman & Jarvik, 1976), RFS = Reasons for Smoking questionnaire (Ikard et al, 1969), SCID = Structured Clinical Interview (Spitzer & Williams, 1989), ADIS = Anxiety Disorders Interview Schedule (DiNardo et al, 1983), ADIS-IV = Anxiety Disorders Interview Schedule (Brown et al, 1994), CAPS = Clinician Administered PTSD scale (Blake et al, 1995), PCL-C = PTSD Checklist Civilian Version (Weathers & Ford, 1996), PDS = Posttraumatic Diagnostic Scale (Foa, 1995), CTS = Conflict Tactics Scale (Straus, Clin Psychol Rev.…”
Section: Theorymentioning
confidence: 99%